2018
DOI: 10.1159/000495411
|View full text |Cite
|
Sign up to set email alerts
|

Molecules Autoinducer 2 and cjA and Their Impact on Gene Expression in <b><i>Campylobacter jejuni</i></b>

Abstract: Quorum sensing is a widespread form of cell-to-cell communication, which is based on the production of signaling molecules known as autoinducers (AIs). The first group contains highly species-specific N-acyl homoserine lactones (N-AHLs), generally known as AI-1, which are produced by AHL synthase. The second group, possessing the characteristic structure of a furanone ring, are known as AI-2. The enzyme responsible for their production is S-ribosylhomocysteine lyase (LuxS). In Campylobacter jejuni, AI-2 and Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Many studies regarding AI-2-mediated quorum sensing have confirmed its role in motility, which includes swimming motility and swarming motility ( Teren et al, 2018 ; Wang et al, 2018 ). The test of cell motility using static cultivation in tubes reveals the relationship between quorum sensing and the motility of ZM4.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies regarding AI-2-mediated quorum sensing have confirmed its role in motility, which includes swimming motility and swarming motility ( Teren et al, 2018 ; Wang et al, 2018 ). The test of cell motility using static cultivation in tubes reveals the relationship between quorum sensing and the motility of ZM4.…”
Section: Resultsmentioning
confidence: 99%
“…QS represents an important mechanism for modulating C. jejuni behavior within its population [ 40 ]. In the present study, ethanolic extracts of cultivated plant material, i.e., “Mattmark” and “Rosavine”, were prepared and fractionated by optimized protocols in order to obtain five fractions rich in salidroside, rosavins, PACs, and/or flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…This can be further seen in changes to O-linked glycosylation of the flagellin proteins where mutant strains defective in flagellin glycosylation demonstrate a decrease in autoagglutination and a reduced biofilm formation potential whilst their motility appears unaffected [29]. A number of regulatory genes impact both motility and biofilm formation, particularly regulators involved in community growth and quorum sensing [30][31][32]. Interestingly, many of the motility-associated genes have also been shown to be critical to the infectivity of C. jejuni, which raises the possibility that there may be pathogenic and biofilm-forming states of this organism that are distinctly regulated.…”
Section: Motility and Chemotaxismentioning
confidence: 98%